2012
DOI: 10.1002/hfm.20374
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics Improvement in Order Selection in a Refrigerated Environment

Abstract: The purpose was to conduct an ergonomics improvement in the order selection process in a refrigerated dairy factory. The workers' task was to pick dairy products to fulfill orders. Plant walkthroughs, unstructured interviews, and direct observation methods were used to study the existing process and problems. Ergonomics intervention was made by introducing a wireless handheld scanning system. A field experiment was carried out to compare the conventional paper pick list with the new system. Results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In particular, the need to develop studies that focus on picking error reduction is pointed out including, for example, consideration of the precise possible trade-offs between the cost of investment in paperless information technology and the return on investment from reduced picking errors. Furthermore, according to De Koster and Van Der Poort (1998) and Poon et al (2009), paperless order picking systems can be a useful strategy to obtain benefits in an order picking warehouse, as validated also in the case studies of some authors in the literature (Berger and Ludwig, 2007;Reif et al, 2010;Yeow and Goomas, 2012). All these studies have concluded that a possible solution that would reduce picking errors and hence improve picking performances is the adoption of paperless picking technologies.…”
Section: Introductionmentioning
confidence: 81%
“…In particular, the need to develop studies that focus on picking error reduction is pointed out including, for example, consideration of the precise possible trade-offs between the cost of investment in paperless information technology and the return on investment from reduced picking errors. Furthermore, according to De Koster and Van Der Poort (1998) and Poon et al (2009), paperless order picking systems can be a useful strategy to obtain benefits in an order picking warehouse, as validated also in the case studies of some authors in the literature (Berger and Ludwig, 2007;Reif et al, 2010;Yeow and Goomas, 2012). All these studies have concluded that a possible solution that would reduce picking errors and hence improve picking performances is the adoption of paperless picking technologies.…”
Section: Introductionmentioning
confidence: 81%
“…Seven articles study perceptual aspects in planning problems for manual order picking (Figure 3). Six of these articles consider human information processing in combination with technical equipment such as pick-by-voice, pick-bylight or even the use of augmented reality technologies (Reif and Walch 2008;Reif and Günthner 2009;Reif et al 2010;Schwerdtfeger et al 2011;Yeow and Goomas 2014;Battini et al 2015a) and a single paper introduces a storage assignment strategy that reduces the amount of information a picker needs during handling (Brynzér and Johansson 1996).…”
Section: Perceptual Factormentioning
confidence: 99%
“…The most traditional way of order picking is with the use of paper pick lists (Yeow and Goomas 2014). Such systems are easy to implement in practice and straightforward to use.…”
Section: Perceptual Factormentioning
confidence: 99%
“…The results show that pick by vision outperformed the conventional picking list in terms of picking time and error rate. Yeow and Goomas (2014) studied technology design by comparing the conventional picking list with a wireless handheld scanning system. The perceptual and psychosocial HF aspects of order pickers were examined using visual/audio feedback and order picker satisfaction, performance being measured by productivity, wellbeing, and quality.…”
Section: Design Levelmentioning
confidence: 99%